Tolerance to heavy metals in filamentous fungi isolated from contaminated mining soils in the Zanjan Province, Iran. (October 2017) - Mohammadian, Elham; Babai Ahari, Asadollah; Arzanlou, Mahdi; Oustan, Shahin; Khazaei, Sayyed Hossein
Abstract: In the present study the population of fungi inhabiting metal contaminated soil samples from lead-zinc mining area was investigated, and their tolerance and biosorption capacity towards Cd, Pb, Zn and Cu were evaluated. Fungal species, including Acremonium persicinum, Penicillium simplicissimum, Seimatosporium pistaciae, Trichoderma harzianum, Alternaria chlamydosporigena and Fusarium verticillioides were isolated. Fungal tolerance was determined by measuring of the "Minimum Inhibitory Concentration", after exposure to increasing concentrations of heavy metal chlorides. Among the test fungi, Trichoderma harzianum was the most tolerant against Cd, Pb and Cu. The Heavy metal content in the fungal biomass was quantified after combustion. The calculated total sorption of heavy metals showed that Acremonium persicinum and Penicillium simplicissimum had the highest accumulation of Zn and Cu, respectively. The data presented in this study should help to use the accumulation potential of some of those fungal species examined for bioremediation of contaminated soils. Highlights: The soils of the mining area had high concentrations of heavy metals. A diversity of filamentous fungi was pinpointed. Among the fungi isolated from these soils, Trichoderma harzianum was the most tolerant to all of the metals tested. Acremonium persicinum and Penicillium simplicissimum had the highest biosorption capacity of heavy metals.